Woman figure in two Ottoman miniature painters - Yildirim, Beste (2016)
This paper aims to display of woman figure in two 18th century Ottoman painters’ works –Abdulcelil Levni and Abdullah Buhari– in terms of art, gender and cultural encounters. My thesis is that although these paintings reveal many important points about the period such as sexuality, gender, perception of woman, symbolic meanings of dresses, sociocultural hierarchies, visual and contextual changes from past to 18th century and also within the century, it should be investigated that how we can scent out similarities of gender issue in focus of female figures in the Ottoman world with the other variations of it for example in Safavid and Greek women representations. In this way, it can be possible to explain this viewpoint with the concepts of encounter, mobility and connection. Thus, this paper’s scope will consist of a struggle to reclaim historical, cultural and artistic perspectives over the main topic.